Combined treatment with zingerone and its novel derivative synergistically inhibits TGF-β1 induced epithelial-mesenchymal transition, migration and invasion of human hepatocellular carcinoma cells. Issue 4 (15th February 2017) - Kim, Young-Joo; Jeon, Youngsic; Kim, Taejung; Lim, Won-Chul; Ham, Jungyeob; Park, Young Nyun; Kim, Tae-Jin; Ko, Hyeonseok
Graphical abstract: Abstract: The epithelial–mesenchymal transition (EMT) is an important cellular process during which polarized epithelial cells become motile mesenchymal cells, which promote cancer metastasis. Ginger, the rhizome of Zingiber officinale, is extensively used in cooking worldwide and also as a traditional medicinal herb with antioxidant, anti-inflammatory and anticancer properties. Several pungent compounds have been identified in ginger, including zingerone, which has anticancer potential. However, the role of zingerone in EMT is unclear. We investigated the synergistic effect of zingerone and its derivative on EMT. Transforming growth factor-beta 1 (TGF-β1) induces the EMT to promote hepatocellular carcinoma metastasis, including migration and invasion. To understand the repressive role of the combination of zingerone and its derivative (ZD 2) in hepatocellular carcinoma metastasis, we investigated the potential use of each compound of ginger, such as zingerone, ZD 2 and 6-shogaol, or the mixture of zingerone and ZD 2 (ZD 2-1) as inhibitors of TGF-β1 induced EMT development in SNU182 hepatocellular carcinoma cells in vitro . We show that ZD 2-1, but not zingerone, ZD 2 and 6-shogaol significantly increased expression of the epithelial marker E-cadherin and repressed Snail upregulation and expression of the mesenchymal marker N-cadherin during initiation of the TGF-β1 induced EMT. In addition, ZD 2-1 inhibited the TGF-β1 induced increase in cell migration and invasion of SNU182 hepatocellular carcinoma cells. Furthermore, ZD 2-1 significantly inhibited TGF-β1 regulated matrix metalloproteinase-2/9 and activation of Smad2/3. We also found that ZD 2-1 inhibited nuclear translocation of NF-κB, activation of p42/44 MAPK/AP1 signaling pathway in the TGF-β1 induced EMT. Our findings provide new evidence that combined treatment with ZD 2, novel zingerone derivative, and zingerone synergistically suppresses hepatocellular carcinoma metastasis in vitro by inhibiting the TGF-β1 induced EMT.